7th Colloquium on Mites - Rainer Ehrnsberger (Soil Organisms, 2010)
During the 6th Colloquium on Mites that was held in Kiel, Czesław Błaszak invited the German-speaking acarologists to Poznań for the next colloquium. After previous colloquia in Germany, Austria and Switzerland, this was the first invitation to a neighbouring country where German is the native language of only a small minority. Since 1983, Professor Błaszak and Professor Dabert, as well as other staff members of the Chair of Animal Morphology at the Institute of Environmental Biology of the Adam Mickiewicz University in Poznań (UAM), have intensive contacts with acarologists of the Universities of Heidelberg, Vechta and Greifswald. They have cooperated in many projects and have taken part in all previous colloquia. Because of this longstanding, fruitful cooperation and existing cooperation agreements with German universities, the invitation to Poland was willingly accepted.